PENGARUH MARKETING MIX DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE OPPO DI MATAHARI SINGOSAREN SURAKARTA - Ratih Witayana Trian Soeripto; Kasidin Kasidin (Riset Manajemen dan Akuntansi, 2021)
The research purpose was determined the effect of Product Quality, Product Price, Promotion and Service Quality on OPPO Smartphone Purchase Decision at Matahari Singosaren Surakarta.This research was conducted in Matahari Singosaren Surakarta with multiple linear regression analysis techniques. The sample is 100 respondents. Based on the analysis results can be known Variable Quality products, Product Price, promotion and Service Quality positively affect oppo smartphone purchasing decisions in Matahari Singosaren Surakarta. Price is the most dominant variable, this can be shown with the highest regression coefficient of 0.638. Based on the results of the determination coefficient, the calculation of the SPSS program obtained a value of R Square = 0.491. This value means that Variable Product Quality, Product Price, Promotion and Service Quality contribute 49.1% to purchasing decisions on OPPO smartphones in Matahari Singosaren Surakarta. While the remaining 50.1% is influenced by other factors outside the researchers.